What can the trove of CSB incident investigations teach us? A detailed analysis of information characteristics among chemical process incidents investigated by the CSB. (March 2021) - Park, Sunhwa; Mendez, Edna; Bailey, James P.; Rogers, William; Pasman, Hans J.; El-Halwagi, Mahmoud M.
Abstract: Understanding the commonalities among previous chemical process incidents can help mitigate recurring incidents in the chemical process industry and will be useful background knowledge for designers intending to foster inherent safety. The U.S. Chemical Safety and Hazard Investigation Board (CSB) reports provide detailed and vital incident information that can be used to identify possible commonalities. This study aims to develop a systematic approach for extracting data from the CSB reports with the objective of establishing these commonalities. Data were extracted based on three categories: attributed incident causes, scenarios, and consequences. Seventeen causal factors were classified as chemical indicators or process indicators. Twelve chemical indicators are associated with the hazards of the chemicals involved in the incidents, whereas five process indicators account for the hazards presented by process conditions at the time of the incident. Seven scenario factors represent incident sequences, equipment types, operating modes, process units, domino effects, detonation likelihood for explosion incidents, and population densities. Finally, three consequence factors were selected based on types of chemical incidents, casualties, population densities, and economic losses. Data from 87 CSB reports covering 94 incidents were extracted and analyzed according to the proposed approach. Based on these findings, the study proposes guidelines for future collection of information to provide valuable resources for prediction and risk reduction of future incidents. Highlights: A brief overview of CSB incidents along with PSM coverage and PHA performance is provided. A systematic approach is developed to extract detailed incident data from CSB reports. For data extraction 17 incident cause, 6 scenario, and 6 consequence factors are proposed. Each incident factor in 87 CSB reports covering 94 chemical incidents is identified. The ultimate purpose is to use the information in future work for inherently safer design.